2006
DOI: 10.1021/bc0600158
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of the p38 MAPkinase Inhibitor SB202190 to Angiogenic Endothelial Cells:  Development of Novel RGD-Equipped and PEGylated Drug−Albumin Conjugates Using Platinum(II)-Based Drug Linker Technology

Abstract: Endothelial cells play an important role in inflammatory disorders, as they control the recruitment of leukocytes into inflamed tissue and the formation of new blood vessels. Activation of p38MAP kinase results in the production of proinflammatory cytokines and the expression of adhesion molecules. P38MAP kinase inhibitors are therefore considered important candidates for the treatment of inflammatory disorders. In the present study, we propose a novel strategy to counteract these processes by delivery of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 29 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…We previously showed that the ULS-based coordination linkage is stable in serum, while drug is released upon competition with sulfur-containing ligands such as glutathione, of which high concentrations are found intracellularly. [17,18] We expect a similar release mechanism for the PTK787-albumin conjugates. In future studies, we will investigate the targeting capacity of these compounds and their tumor growth inhibitory properties.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…We previously showed that the ULS-based coordination linkage is stable in serum, while drug is released upon competition with sulfur-containing ligands such as glutathione, of which high concentrations are found intracellularly. [17,18] We expect a similar release mechanism for the PTK787-albumin conjugates. In future studies, we will investigate the targeting capacity of these compounds and their tumor growth inhibitory properties.…”
mentioning
confidence: 74%
“…Our drug-ULS linkage strategy is furthermore applicable to other drugs and carriers. [17][18][19] Optimization of the ligand-targeted drug-delivery conjugates by additional PEG modification not only improved pharmaceutical properties such as solubility and aggregation, but will also positively affect the behavior in vivo.…”
mentioning
confidence: 99%
“…Moreover, since our results suggest that the anti-anabolic activity of TNF-a is at least partially mediated by the p38 MAPK pathways, therapeutics targeting p38 MAPK may be able to stimulate neochondrogenesis in the damaged joints as well as to inhibit joint destruction. In fact, several p38 inhibitors are currently in clinical trials for RA [39][40][41]. However, it should be noted that SB203580 only partially restored the catabolic effects of TNF-a at 0.3 lM, and that higher doses of the compound rather abrogated its anticatabolic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin conjugates can further be modified by PEGylation to impart hydrophilicity to improve the blood residence of conjugates (Temming, Lacombe, Schaapveld, et al, 2006;Temming, Lacombe, van der Hoeven, et al, 2006). Additionally, one can also go for coupling of targeting ligands such as cyclic or acyclic RGD, lactosamine and folate to the albumin to impart targeting potential to the conjugates (Dosio et al, 2009;Fiume et al, 2005;Temming, Lacombe, Schaapveld, et al, 2006;Temming, Lacombe, van der Hoeven, et al, 2006;Temming, Meyer, Zabinski, et al, 2006). The high endogenous availability of albumin in blood has been conveniently exploited to prepare in situ albumin-drug conjugates using chemically modified drugs with maleimide group which binds to serum albumin when injected in blood stream.…”
Section: Albumin-drug Conjugatesmentioning
confidence: 99%